Determinación de la incidencia y severidad causada por el manchado de grano en cultivares de arroz (Oryza sativa L.) en el cantón Babahoyo - Bazán Reyes, Carlos Javier (2025)
Rice cultivation (Oryza sativa L.) plays a fundamental role in Ecuador's economy and food security, being one of the main sources of income for rice producers in the country. However, its production faces significant challenges due to phytosanitary factors such as grain discoloration, a disease that affects both the quality and yield of the crop. This study aimed to determine the incidence and severity caused by grain discoloration in rice cultivars in the Babahoyo canton and to select the cultivars with the lowest disease index (DI) for grain discoloration. The study used 81 rice cultivars, which were evaluated for incidence, severity, and disease index of grain discoloration. For the analysis of the variables, analysis of variance (ANOVA) and Tukey’s test (p > 0.05) were applied. A Euclidean analysis was also performed to determine the similarity in response to grain discoloration among the cultivars. To select the individuals with the least reaction, the IRRI (1996) scale was used, which allowed classification into reaction groups: Resistant–Tolerant, Moderately Tolerant, and Susceptible.